Selective Electrooxidation of Glycerol Into Value-Added Chemicals: A Short Overview - Coutanceau, Christophe; Baranton, Stève; Kouamé, Roméo S. Bitty (Frontiers in Chemistry, 2019)
A comprehensive overview of the catalysts developed for the electrooxidation of glycerol with the aim of producing selectively value-added compounds is proposed in the present contribution. By presenting the main results reported in the literature on glycerol electrooxidation in acidic and alkaline media, using different kind of catalytic materials (monometallic catalyst based on platinum group metal and non-noble metals, multimetallic alloys or modification of surfaces by adatoms, etc.) and under different experimental conditions, some general trends concerning the effects of catalyst composition and structure, of reaction medium and of the electrode potential to favor the enhancements of the activity for the glycerol oxidation reaction and of the selectivity towards a unique value-added product will be presented and discussed. The objective is to provide a guideline for the development of electrochemical systems which allow performing the electrooxidation of glycerol at the rate and selectivity possible as high as possible.